2009
DOI: 10.1002/met.144
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating humidity pseudo‐observations derived from the cloud profiling radar aboard CloudSat in ALADIN 3D‐Var

Abstract: This paper describes an experimental procedure for assimilating CloudSat Cloud Profiling Radar (CPR) observations in ALADIN 3D-Var through the use of humidity pseudo-observations derived from a one-dimensional Bayesian analysis. Cloud data are considered as binary occurrences ('cloud' vs 'no-cloud'), which makes the approach feasible to be extended to other cloudiness observations, and to any other binary observation in general. A simple large-scale condensation scheme is used for projecting the prior informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 50 publications
(42 reference statements)
3
16
0
Order By: Relevance
“…HARMONIE is the name given to the ALADIN core-based limited-area model with the HIRLAM community-developed framework. It is not operational at the Norwegian Meteorological Institute, but it has been already used for observations impact studies [Storto and Tveter, 2009;Storto and Randriamampianina, 2010].…”
Section: Regional Modelmentioning
confidence: 99%
“…HARMONIE is the name given to the ALADIN core-based limited-area model with the HIRLAM community-developed framework. It is not operational at the Norwegian Meteorological Institute, but it has been already used for observations impact studies [Storto and Tveter, 2009;Storto and Randriamampianina, 2010].…”
Section: Regional Modelmentioning
confidence: 99%
“…Experimental assimilation of the Atmospheric Radiation Measurement programme (ARM) cloud radar observations combined with the ground-based precipitation measurements and GPS total column water-vapour retrievals has been proposed by Lopez et al (2006) using a 2D-Var technique (the second dimension being time). Storto and Tveter (2009) used an experimental procedure to assimilate the cloud fraction from CloudSat Cloud Profiling Radar (CPR) in a limited-area 3D-Var system through the use of humidity pseudoobservations derived from a one-dimensional Bayesian analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The AMMA campaign has shown that improvements in the upper-air observation network are possible and can in some cases be relatively inexpensive ), but sufficient funds and staff are required. The shortage of radiosonde data makes effective use of satellite data particularly important: the use of novel techniques such as those discussed in Storto and Tveter (2009) and Kostka et al (2014) are of particular interest as there is potential for improved representation of subgrid-scale processes in (re)analyses for a relatively small investment.…”
Section: Discussionmentioning
confidence: 99%
“…One possible avenue is by the assimilation of clouds into three-/four-dimensional variational data assimilation (3D/4DVAR) systems. Storto and Tveter (2009) illustrate how a pseudoobservation assimilation scheme using CloudSat data has a clear benefit on a number of different fields in a 3DVAR assimilation scheme. They also suggest that the technique might be extended to be used for other sources of data including satellite-borne infrared sensors.…”
Section: ) Behavior Of the Zonal-mean Itdmentioning
confidence: 99%